An intelligent system of content-based image retrieval for crime investigation. (2015) - Shriram, K.V.; Priyadarsini, P.L.K.; Baskar, A.
Crimes in the modern world have been increasing dramatically in proportion with technological growth. In many situations, investigators have a sketch of the criminal, generated from the details given by the eye witnesses. There is a need of a better methodology for identifying the culprits from those images. Nowadays, RAM and memory sizes have become huge and in turn, there is a tremendous increase in the size of the databases. Investigators have huge datasets with details, photographs, images of the criminals or crime scenes and this is the second important consideration. Image search has become highly challenging task in these dense database environments. Accuracy and speed are two important factors for this type of image searches. We propose a compact embedded search engine to search and extract images from these data bases, using a content-based image retrieval (CBIR) algorithm.